PEMANFAATAN LIMBAH PERTANIAN SEBAGAI MULSA ORGANIK UNTUK MENDUKUNG PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG DAUN (Allium fistulosum L.) - Novriani, Novriani; Danial, Ekawati; Ariyadi, Rahmat (Universitas Muhammadiyah Palembang, 2018)
To reduce the process of water loss in crop cultivation leaf onion on dry land is to use agricultural waste as mulch. Mulch is useful for maintaining soil moisture, soil temperature and loss of nutrients. This study aims to determine the effect of organic mulch and mulch which is appropriate to help the growth and production of leaf onions. This research was conducted at the Experimental Garden of the Faculty of Agriculture, Baturaja University, Baturaja Timur District, Ogan Komering Regency, South Sumatra Province. When the study was conducted in April to June 2017. The study used a non factorial completely randomized design analysis. P0 = Without Mulch, P1 = Rice Straw, P2 = Coffee Skin, P3 = Corn Stems and P4 = Alang-Alang. Variables observed were plant height, number of plants, wet weight of plants, height of leaves and number of leaves. Based on the results of the study of the effect of various organic mulch on the growth and production of leaf onion plants, it can be concluded that: The provision of organic mulch can affect the growth and production of leaf onion plants. The use of corn stem mulch is a treatment that can help growth and increase 3.62% of the production of leaf onion plants. Untuk mengurangi proses kehilangan air pada budidaya tanaman bawang daun di lahan kering adalah dengan memanfaatkan limbah pertanian sebagai mulsa. Mulsa bermanfaat untuk menjaga kelembaban tanah, suhu tanah dan kehilangan hara. Penelitian ini bertujuan untuk mengetahui pengaruh mulsa organik dan mulsa yang tepat untuk membantu pertumbuhan dan produksi bawang daun. Penelitian ini dilaksanakan di Kebun Percobaan Fakultas Pertanian Universitas Baturaja, Kecamatan Baturaja Timur Kabupaten Ogan Komering Provinsi Sumatera Selatan. Waktu penelitian dilakukan pada bulan April sampai Juni 2017. Penelitian menggunakan Analisis Rancangan Acak Lengkap non Faktorial. P0 = Tanpa Mulsa, P1 = Jerami Padi, P2 = Kulit Kopi, P3 = Batang Jagung dan P4 = Alang-Alang. Peubah yang diamati tinggi tanaman, jumah anakan, berat basah tanaman, tinggi seludang dan jumlah daun. Berdasarkan hasil penelitian pengaruh berbagai mulsa organik terhadap pertumbuhan dan produksi tanaman bawang daun maka dapat disimpulkan bahwa : Pemberian mulsa organik dapat mempengaruhi pertumbuhan dan produksi tanaman bawang daun. Penggunaan mulsa batang jagung merupakan perlakuan yang dapat membantu pertumbuhan dan meningkatkan 3,62 % produksi tanaman bawang daun.